(untitled) (Materiali di Estetica. Terza serie, 2014)
Cinema is a constant feature in the thinking of Jean-François Lyotard. The essay Acinema (1973) is his most known contribution to cinema, but if we stop here, we risk having a partial idea of the path of the philosopher totally linked to experimental film. After two decades, the analysis of Idea of a sovereign film (1995) helps us to find the acinema in the windows of sovereign realities opened inside narrative and representative movies.